Poetry on wheels - Hopkins, Lee Bennett; Aloise, Frank (Garrard Publishing Company Champaign, Illinois, 1974)
A collection of poems about cars, buses, trucks, trains, subways, building machinery, boats, airplanes, and rocket ships.
7 - 9 years
Keywords: Tansporation -- Juvenile poetry; American Poetry -- Collections